Spiritual Perfection of Adolescents in Single-Parent Families - Shaamirova Yulduzkhan Kabildjanovna (Open Academia, 2023)
This article describes the life of teenagers in single-parent families, its problems and the importance of spirituality in solving these problems
Keywords: Loyalty; trust; difficulty